Status of Bottom Trawl Fishery In Kerala (South India) B - B., Madhusoodana Kurup; Rajasree, Radhika (Fishery Technology, 2025)
The total number of bottom trawlers operated from 11 harbours in Kerala comprising 6 major and 5 minor harbours were enumerated during August 2000 to July 2001. A total of 4960 bottomtrawlers were found to operate during the study period. On an average, 1542 trawlers were landed per day in Aug-2000 while it was only 738 in Nov-00 being the lowest. 40-50’LOA size class vessels (38%) dominated among the trawlers operated in Kerala followed by 31-40’ (30%). Total bottom trawl landings were quantified as 2,46,116 tonnes that accounts for 46% of the total marine fish landings and 87% under total mechanised sector during 2000-01. The annual average CPUE was estimated to be 891kg with a catch/hr of 53 kg. Highest share of the trawl landings was reckoned from 21-40 m depth contributing to 24.5% while highest CPUE from bottom trawl net was also recorded from the same depth.